Development and Validation of a Simple and Rapid UPLC–MS Assay for Valproic Acid and Its Comparison With Immunoassay and HPLC Methods. Issue 2 (April 2016) - Zhao, Mingming; Li, Guofei; Qiu, Feng; Sun, Yaxin; Xu, Yinghong; Zhao, Limei
Abstract : Background: Valproic acid (VPA), a widely used antiepileptic drug, has a narrow therapeutic range of 50–100 mcg/mL and shows large individual variability. It is very important to monitor the trough concentration of VPA using a reliable method. Therefore, the aim of this study was to develop and validate a rapid ultraperformance liquid chromatographic–mass spectrometry (UPLC–MS) method for quantification of VPA in human serum and to compare with fluorescence polarization immunoassay (FPIA), chemiluminescence microparticle immunoassay (CMIA), and high-performance liquid chromatography (HPLC) methods. Methods: The method included extraction of VPA in serum by deproteinization with acetonitrile. The analysis was performed using an EC-C18 column (2.7 μm, 4.6 × 50 mm) under isocratic conditions with a mobile phase of acetonitrile/water (containing 0.1% formic acid) (45/55, vol/vol) at a flow rate of 0.6 mL/min. The detection was performed on a triple-quadrupole tandem mass spectrometer using an electrospary probe in the negative ionization mode. The method was validated by studies of selectivity, linearity, lower limit of quantification, accuracy, precision, recovery, matrix effect, and stability. Furthermore, all the 4 methods including FPIA, CMIA, and HPLC were subsequently used to assay the VPA concentration in 498 clinical serum samples collected from patients who received VPA. These methods were compared by Deming regression and Bland–Altman analysis. Results: The retention time of VPA was 2.09 minutes. The calibration curve was linear over the concentration range of 1–200 mcg/mL, with a lower limit of quantification of 1 mcg/mL. The interday and intraday precision (RSD %) was less than 4.6% and 4.5%, respectively, and the accuracy (RE %) was below 7.9%. The recoveries and matrix effect of VPA at concentrations of 2, 50, and 160 mcg/mL met the requirement for the analysis of biological samples. No obvious degradation of VPA was observed under various storage conditions including room temperature for 12 hour, 3 freeze–thaw cycles, and −20°C for 3 months. Regression analysis showed that the correlation coefficients for the UPLC–MS versus FPIA, CMIA, and HPLC were 0.989, 0.988, and 0.987, respectively. The results of agreement tests between UPLC–MS and other methods showed that the mean difference of UPLC–MS and FPIA was −1.4 mcg/mL and 95% confidence interval of −7.7 to 4.9 mcg/mL, and the values for UPLC–MS and CMIA were −0.8 mcg/mL and −7.5 to 5.8 mcg/mL, for UPLC–MS and HPLC were 1.1 mcg/mL and −5.7 to 7.9 mcg/mL. Conclusion: The rapid UPLC–MS method we developed showed a good analytical performance required for therapeutic drug monitoring, leading to potential improvements in patient care and laboratory management. Compared with the FPIA, CMIA, and HPLC methods, the UPLC–MS method correlated well and displayed comparable VPA concentrations.